Efektivitas Supervisi Kepala Sekolah dalam Meningkatkan Disiplin dan Kinerja Guru di Sekolah Dasar - Lenny Maryani (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to analyze the effectiveness of supervision carried out by the principal in improving teacher discipline and performance at the elementary school level. Supervision is seen as an important strategy in developing teacher professionalism and improving the quality of education. Through a review of literature and studies of various previous studies, it was found that structured, collaborative, and reflective supervision practices can encourage improved teacher performance in terms of planning, implementing, and evaluating learning. In addition, supervision based on Islamic values, effective communication, and an integrated quality management approach also contribute positively to teacher work discipline and the efficiency of the learning process. The results of the analysis show that principals who carry out their supervisory role actively and strategically can create a conducive work environment and support teacher professional growth. Thus, the effectiveness of principal supervision is a crucial factor in building a disciplined work culture and improving teacher performance in elementary schools.